The Role of Learning Orientation in the Context of Sustainable Human Resources Development - Simona-Valentina Pașcalau; Ramona-Mihaela Urziceanu (Agora International Journal of Economical Sciences (AIJES), 2022)
The belief that learning and innovation are important to flourish in competitive and dynamic situations has sparked an increase in interest in the learning process within the organization during the past two decades. The actions that the entire company engages in to generate and apply knowledge to gain a competitive advantage are included in a firm's learning orientation.
Keywords: 330